Writing my wrongs : life, death, and redemption in an American prison - Senghor, Shaka (Convergent Books, 2016)
"During his nineteen-year incarceration [for murder], seven of which were spent in solitary confinement, Senghor discovered literature, meditation, self-examination, and the kindness of others--tools he used to confront the demons of his past, forgive the people who hurt him, and begin atoning for the wrongs he had committed. Upon his release at age thirty-eight, Senghor became an activist and mentor to young men and women facing circumstances like his"--Dust jacket flap.